The theological study of Divine Names in reference to Ayah no 255 of Surah al-Baqarah - Dr. Hafsah Ayaz Qureshi,; Dr. Sami ul Haq,; Ms. Amira Sami,; Ms. Syeda Ujala Zahid, (Al-Qanṭara, 2023)
Abstract Ayah no 255 of Surah al-Baqarah is known as “Ayat-al-kursi”, which is among the most well-known ayahs of the Qur'an and is frequently memorized due to its vivid and emphatic portrayal of Allāh's Attributes and Power. This research is a Theological study of “Ayat-al-kursi” and elaborates on the Majesty and Perfection of the Supreme Being of Allāh. The research reveals remarkable truths about Allāh’s Majesty and Grandeur. In this study, the ayah is divided into ten phrases, and discussed each phrase in detail by giving the linguistic and terminological meaning of each attribute of Allāh. It is concluded that Allāh is one, has no partner, is unique and there is no one else like Him; He is distinct and eternal, having no equivalent. He is the First, having no start; no beginning; the Everlasting, having no end; and the Eternal, having no end. He is First and Last forever and is not subject to any edict set by specific boundaries or times. Keywords: Ayat-ul-Kursi, Majesty of Allāh, Theology